Overseas Pilipino workers guide - Garming, Maximo B.; Llamanzares, Ma. Llana N. (National Center for Protection of Overseas Pilipino Workers, 1990)
Based on the proceedings of the international seminar on "Migrant workers: New Area of concern for Labour Unions". This guidebook evaluates policies, and program of actions that will develop and improve the protection of migrant workers in the Third World countries. A helpful reference about the problems and difficulties of working abroad. Provides information about the location and contact persons of the embassy of the Philippines in different countries.